Effective team leadership for engineers - Wellington, Pat; Foster, Niall (The Institution of Engineering and Technology, 2009)
The book contains 15 chapters and is divided into five parts. The first part presents key principles of leadership such as responsibilities of team leaders. The second part presents creating continuous improvement environment. The third part presents practical implementation such as operational management; recruitment; motivation; appraisal; performance reward; and problem solving activities. The fourth part presents communication strategy and the fifth part presents career management.